A new species of microphallid (Trematoda: Digenea) infecting a novel host family, the Muraenidae, on the northern Great Barrier Reef, Australia - Kudlai, Olena; Cribb, Thomas H; Cutmore, Scott C (Systematic parasitology, 2016)
A new species of microphallid, Longiductotrema tethepae n. sp., is reported from a muraenid eel Gymnothorax pseudothyrsoideus (Bleeker) on the northern Great Barrier Reef. The new species is described based on adults from Gy. pseudothyrsoideus and metacercariae from a grapsid crab, Grapsus albolineatus Latreille in Milbert, collected from off Lizard Island, Queensland, Australia. The new species is assigned to Longiductotrema Deblock & Heard, 1969 based on morphological characters (presence of a cirrus-sac; a long metraterm, intensively ensheathed by gland-cells; an entirely postcaecal uterus; vitellarium composed of two lateral clusters each of about ten follicles, situated in the testicular and post-testicular areas). Longiductotrema tethepae n. sp. is the third species assigned to the genus, differing from its congeners in having a distinctly larger body dimensions, a smaller pharynx in relation to oral sucker, the anterior limits of the vitelline fields at the level of the testes (vs at the level of the ovary) and in its parasitism of a muraenid fish (vs birds). Additionally, the new species differs from L. floridense Deblock & Heard, 1969 in having a shorter metraterm and from L. scandolensis Deblock & Bartoli, 1988 in having a less elongate forebody in relation to body length, shorter caeca and prepharynx, and slightly larger eggs. Phylogenetic analyses, based on partial 28S rRNA gene sequences, showed that the present species is sister to all other microphallids for which sequence data are available. This is the fourth report of a microphallid from a marine eel, the first from the Muraenidae Rafinesque and the first from a marine fish in the Indo-west Pacific. A summary of all species of the Microphallidae parasitising fish is provided.
Keywords: Species Specificity; Trematoda; RNA, Ribosomal, 28S; Eels; Female; Animals; ženské pohlaví; mužské pohlaví; druhová specificita; Male; Phylogeny; Austrálie; zvířata; fylogeneze; Australia; Anguilliformes; RNA ribozomální 28S